Development of Smart Waste Bin with Segregation System Protoype - farhan, Amirulfarhanfauzilan; AMERUDDIN, AMIRA SARYATI (Enhanced Knowledge in Sciences and Technology, 2024)
In the current era of rapid global development, the substantialgeneration of electronic, plastic, and biodegradable waste poses acritical environmental challenge, especially in developing nations wherewaste management is often neglected. Ineffective waste disposal canlead to pollution, health risks, and resource waste. Therefore, the smartwaste bin with segregation system prototype connected with Iotdashboard is built to overcome the problems. This work utilizes anArduino UNO R3 microcontroller, inductive proximity sensors for metaldetection, a moisture sensor for gauging waste moisture, and ultrasonicsensors for measuring waste levels together with Servomotors also areenabled to precise the sorting control for the waste collection. Thesystem is integrated with Node-RED user-friendly interface for realtime monitoring. The seamless coordination between the sensor'sdetection and precise servomotor control ensures accurate sorting ofeach waste category into designated compartments for furtherprocessing or disposal. This automation system improves waste sortingeffectiveness and boosts the overall efficiency of waste managementsystems, promoting recycling initiatives and encouragingenvironmentally responsible practices for wet waste, metal waste, andother waste categories. The system’s potential usage in public spacesoffers a solution to optimize waste management and contribute to acleaner and more environmentally conscious public infrastructure.furthermore, .system's usability can be enhanced to provide a platformfor effective data management and analysis related to wastemanagement.